2019
DOI: 10.1177/1350650119864482
|View full text |Cite
|
Sign up to set email alerts
|

Study on tribo-chemical and fatigue behavior of 316L austenitic stainless steel in torsional fretting fatigue

Abstract: Fretting fatigue is a complex tribological phenomenon that can cause premature failure of connected components. Combining with the effects of tribological and fatigue, the components have premature fracture, which ultimately leads to disastrous consequences. In this work, the fretting fatigue tests of 316L austenitic stainless steel have been carried out with same normal load and varied torsional torques. The results indicate that the fretting fatigue life significantly depends on the torque amplitude, wear de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Vast differences were observed in the effects of oxygen on the wear rates of the two materials. Xu et al [295] studied on tribochemical and fatigue behavior of 316L stainless steel by using a torsional LFV100-T500-HH servo fatigue tester. By XPS analysis, they found that the extent of oxidation in the fretting damage zone was affected by the amplitude of relative displacement.…”
Section: Fretting Wear and Subsurface Damagesmentioning
confidence: 99%
“…Vast differences were observed in the effects of oxygen on the wear rates of the two materials. Xu et al [295] studied on tribochemical and fatigue behavior of 316L stainless steel by using a torsional LFV100-T500-HH servo fatigue tester. By XPS analysis, they found that the extent of oxidation in the fretting damage zone was affected by the amplitude of relative displacement.…”
Section: Fretting Wear and Subsurface Damagesmentioning
confidence: 99%
“…According to different types of fatigue loads, there are three types of fretting fatigue: fretting fatigue of tension-compression, torsion, and bending [8]. Most of the existing studies have focused on the fretting fatigue of tension-compression and torsion, while studies are limited on the fretting fatigue of bending [9][10][11][12]. Ebaraa et al studied the bending fretting fatigue behaviors of Ti-6Al-4V [13].…”
Section: Introductionmentioning
confidence: 99%
“…Leonard et al 15 developed the finite discrete element model (FDME), which accurately predicted the wear amount obtained in the experimental measurement through the energy dissipation method, and the changes in the energy dissipation rate and wear amount were analyzed. Xu et al 16 performed the fretting fatigue experiment on 316L austenitic stainless steel under the same normal load and different torques. The results show that the torque amplitude, wear degree, and energy dissipation significantly affected the fretting fatigue life.…”
Section: Introductionmentioning
confidence: 99%